Conjunctive surface water and groundwater management under climate change - Zhang, Xiaodong (Frontiers in Environmental Science, 2015)
Climate change can result in significant impacts on regional and global surface water and groundwater resources. Using groundwater as a complimentary source of water has provided an effective means to satisfy the ever-increasing water demands and deal with surface water shortages problems due to robust capability of groundwater in responding to climate change. Conjunctive use of surface water and groundwater is crucial for integrated water resources management. It is helpful to reduce vulnerabilities of water supply systems and mitigate the water supply stress in responding to climate change. Some critical challenges and perspectives are discussed to help decision/policy makers develop more effective management and adaptation strategies for conjunctive water resources use in facing climate change under complex uncertainties.